P067 Tofacitinib impairs monocyte-derived dendritic cell differentiation in rheumatoid arthritisand psoriatic arthritis. (March 2019) - Marzaioli, V; Canavan, M; Floudas, A; Wade, S; Low, C; Veale, DJ; Fearon, U
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: Tofacitinib is an oral Janus kinase inhibitor, recently approved for the treatment of rheumatoid arthritis (RA) and psoriatic arthritis (PsA). Although its mechanism of action has been explored in circulating cells, including neutrophils and lymphocyte, its effect on dendritic cells development and function remains still to be elucidated. Monocyte-derived dendritic cells (Mo-DC) are a subset of inflammatory DC derived from circulating monocytes with a key role in inflammation and infection. Objectives: The aim of this project is to evaluate the effect of Tofacitinib on inflammatory Mo-DC differentiation from RA and PsA patients, an important step in innate immunity. Methods: Monocytes were isolated from blood of healthy donor (HC), RA and PsA patients by magnetic separation and differentiated in the presence of GM-CSF/IL-4 cocktail for 7 days. To evaluate the effect of Tofacitinib on Mo-DC differentiation, monocyte were pre-treated with 1 µM Tofacitinib (or DMSO as control). CD209 (immature DC marker) was evaluated by flow cytometry in the CD11c + population. Non-specific macropinocytosis (using Lucifer Yellow) and receptor-mediated endocytosis (using DQ TM Ovalbumin) were investigated by flow cytometry. The effect of Tofacitinib on NADPH oxidases (NOX) 5 and 2 expression, known players in Mo-DC differentiation, was evaluated by Western blot analysis. Finally, the frequency of CD209 + cells and their chemokine receptor expression (CXCR3/4/5 and CCR6/7) were evaluated by flow cytometry in peripheral blood (PBMC), synovial fluid (SFMC) mononuclear cells and synovial tissue cell suspensions from RA and PsA patients. Results: Pre-treatment of Mo-DC with Tofacitinib inhibited Mo-DC differentiation in RA and PsA patients, as evident by reduced CD209 marker expression. The decreased ability of monocytes to differentiate into DC in the presence of Tofacitinib was translated into a functional impairment of endocytic ability, in particular in PsA patients, as observed by the decreased uptake of both DQ TM Ovalbumin and Lucifer Yellow. In addition, Tofacitinib decreased NOX5 and increased NOX2 protein expression in Mo-DC of PsA and RA Mo-DC, altering the NOX2/NOX5 balance. Finally, we identified CD209 + cells in the periphery of RA and PsA patients, which were enriched in SFMC and synovial tissue cell suspension, and presented with an increased expression of CCR7 and CXCR3/5. Conclusions: Together, these observations suggest a novel mechanism of action of Tofacitinib in RA and PsA, by inhibiting Mo-DC development, which may alter migration of DC to the joint and subsequent activation of the immune response. Disclosure of Interest: V. Marzaioli Grant/research support from: Pfizer, M. Canavan: None declared, A. Floudas : None declared, S. Wade : None declared, C. Low : None declared, D. Veale: None declared, U. Fearon Grant/research support from: Pfizer.